THE TASTY OF BRAND PRODUCTS FOR MICRO, SMALL AND MEDIUM ENTERPRISES “BRANCH PURNAMA” - Emmywati, Emmywati; Masyhuri, Mohammad Ali; Setyawan, Mochamad Ardi; Suprihandari, Miya Dewi (Nindikayla Institute, 2023)
The word “Branch Purnama” is a word that is often read, heard and is a favorite of consumers and lovers of local roadside food in Indonesia, especially in East Java. The word has automatically become a